2008
DOI: 10.1016/j.parkreldis.2008.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine β-hydroxylase −1021C>T association and Parkinson's disease

Abstract: A single nucleotide polymorphism in the promoter region of the dopamine β-hydroxylase gene (DBH -1021C>T; rs1611115) is reported to regulate plasma enzyme activity levels. This variant has also been the focus of two large association studies in Parkinson's disease yielding conflicting results. We examined this association in four Caucasian patient-control series (n=2696). A modest protective association was observed in the Norwegian series (OR=0.81, p=0.03; n=1676), however the effect was in the opposite direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
(16 reference statements)
1
14
0
Order By: Relevance
“…For rs1611115, combined results from all four of the studies included indicated that this SNP is not statistically associated with an increased PD risk, consistent with the results from two individual studies authored by Chun L.S. et al (2007) [28] and Ross O. et al (2008) [30] but not with those of the other two studies (Fig. 2B).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For rs1611115, combined results from all four of the studies included indicated that this SNP is not statistically associated with an increased PD risk, consistent with the results from two individual studies authored by Chun L.S. et al (2007) [28] and Ross O. et al (2008) [30] but not with those of the other two studies (Fig. 2B).…”
Section: Discussionsupporting
confidence: 85%
“…These studies were published from 1996 to 2016. Among them, 25 studies involved Caucasian populations (AD: n = 5 [20][21][22], PD: n = 3 [28][29][30], SCZ: n = 17 [34-37, 44-46, 48]), and 16 studies involved Asian populations (AD: n = 2 [23,24], PD: n = 4 [31][32][33], SCZ: n = 10 [38-43, 47, 49]). Additionally, two diagnostic criteria were used among the AD studies included (DSM-IV [56] and NINCDS-ADRDA [57]), two criteria were used for PD studies (UK PD Society Brain Bank Clinical Diagnostic Criteria (UK-PDSBB) [58] and Standard for Second National conference on Cone Diseases), and three criteria were used for SCZ studies (DSM-IV [56], DSM-III-R [56] and ICD-10 [59]).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the staggering 8031 reported polymorphisms, less than 20 have been positively associated with the disease; however, the functional implications of these polymorphisms are unclear (Table ) (Tang et al ; Tang et al ; Ross et al ; Kamata et al ; Cubells et al ; Mustapic et al ). Of the total genetic variants, over 7000 are upstream/downstream or within intronic elements.…”
Section: Genetic Variations In the Dβh Genementioning
confidence: 99%
“…Comprehensive meta‐analyses, compiling data from multiple ethnicities, have shown that this polymorphism may not be associated with PD. Interestingly, however, authors suggest that this SNP has been linked with a delay in the age of onset of PD in several different studies (Ross et al ; Kang et al ). Ross and co‐workers suggest that this may be because of higher availability of DA in the earlier stages of the disease, yielding the belief that lower DβH levels may be protective (Ross et al ).…”
Section: Dβh In Neurodegenerative Diseasementioning
confidence: 99%